A comparison of bone mineral density in amateur male boxers and active non-boxers - Bolam, K. A.; Skinner, T. L.; Sax, A. T.; Adlard, K. N.; Taaffe, D. R. (International Journal of Sports Medicine, 2016)
To examine the site-specific osteogenic effect of upper limb impact-loading activity we compared the forearm and arm bone mineral density (BMD) of male boxers to that of active controls. A cross-sectional study was performed with 30 amateur male boxers (aged 18-44 years) and 32 age-matched, non-boxing, active controls. Participants had their regional and whole body BMD and bone mineral content (BMC) assessed by dual-energy X-ray absorptiometry. Hand grip strength, testosterone, oestradiol, sex hormone-binding globulin, vitamin D, lean and fat mass, and past and current physical activity were also assessed. Forearm and arm BMD were 1.5-2.2% higher in boxers than the control group although this was not statistically significant (p>0.05), with no significant difference for BMC (p>0.05). There were no differences between groups for spine, hip, or whole body BMD or BMC, or for body composition or hormone status. Within the arms, lean mass was associated with BMD and BMC in both boxers and the control group (BMD, r=0.60-0.76, p<0.001; BMC, r=0.67-0.82, p<0.001). There were no significant differences between amateur boxers and the control group for upper limb BMD and BMC. However, muscle mass appears to be particularly important to bone health of the upper limbs.